2006
DOI: 10.1080/01140671.2006.9514404
|View full text |Cite
|
Sign up to set email alerts
|

Use of near infrared spectra to identify cultivar in potato(Solarium tuberosum)crisps

Abstract: Near infrared spectra were collected of potato crisps from potato (Solanum tuberosum) cultivars 'Whitu' and 'Fianna'. Pattern recognition techniques were used to classify the spectra. Linear discriminant analysis performed as well as piecewise linear discriminant analysis in identifying the potato tuber variety used to produce the potato crisps. The success rate in separating the spectra into respective classes using discriminant analysis is 93%. This suggests that it is possible to use near infrared analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…On the other hand, NIRS prediction of reducing sugars, sucrose and total sugars was rather poor, as shown by the low r 2 pred values (Haase 2011). A study into the potential of NIRS to identify cultivars of potato used in the production of crisps has shown that discriminant analysis can separate the spectra into different classes corresponding to cultivars with a 93% success rate, suggesting that NIRS could be used to identify cultivars within single batches of potato crisps (Yee et al 2006). It has also been shown that NIRS can provide an accurate prediction of N concentrations, with a single global calibration, across a wide range of different plant species (Shepherd et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, NIRS prediction of reducing sugars, sucrose and total sugars was rather poor, as shown by the low r 2 pred values (Haase 2011). A study into the potential of NIRS to identify cultivars of potato used in the production of crisps has shown that discriminant analysis can separate the spectra into different classes corresponding to cultivars with a 93% success rate, suggesting that NIRS could be used to identify cultivars within single batches of potato crisps (Yee et al 2006). It has also been shown that NIRS can provide an accurate prediction of N concentrations, with a single global calibration, across a wide range of different plant species (Shepherd et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, various studies used a variety of preprocessing and chemometric approaches to differentiate plant species. Yee et al [ 29 ] employed NIR spectra in conjunction with LDA to discriminate potato tuber varieties, with a classification accuracy of 93%. Chen et al [ 30 ] used SVM to differentiate three tea varietals.…”
Section: Resultsmentioning
confidence: 99%
“…LDA combined with principal component analysis (PCA) as a pre-processing method had the best classification accuracies. Yee et al(2006) used NIR spectra to identify the potato tuber variety based on LDA pattern recognition techniques. The success rate in separating the spectra into respective classes was 93%.…”
Section: Introductionmentioning
confidence: 99%